Factors associated with COVID-19 vaccine hesitancy after implementation of a mass vaccination campaign - Gomes, Inês Afonso (2022)
Funding Information: Funding: The present publication was funded by Fundação Ciência e Tecnologia, IP national support through CHRC (UIDP/04923/2020). Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.